Peer support as a pathway for reducing FOMO: a theoretical synthesis of self-determination and broaden-and-build frameworks - Hamidi Izwan, Eisya Sofea; Muhammad Sandi, Nur Farha Najaha; Sufian, Nur Hafizah; Mohamad Nadzri Shah, Nur Nayli Batrisyia; Muhamad Zaib, Nur Syahmina Athirah; Abdul, Adibah; Abdullah, Shajaratul Najwa; Lourdunathan, Pamilia (IIUM Press, 2025)
This study investigates the potential of peer support group interventions to reduce Fear of Missing Out (FOMO) among adolescents in an orphanage, using Positive Psychology frameworks, specifically Self-Determination Theory and the Broaden-and-Build Theory. The aim was to enhance emotional well-being and lower FOMO through mindfulness practices, gratitude exercises, and social support mapping integrated into organised peer support sessions. A mixed-methods approach was employed, including a needs analysis, pre- and post-intervention assessments with the FOMO Scale, and qualitative feedback. Eight adolescents aged 12 to 16 from an orphanage participated in three peer support sessions. Quantitative results indicated modest reductions in FOMO among participants who attended all sessions, whereas inconsistent attendance produced mixed outcomes. Qualitative data highlighted peer conformity pressures and unequal participation as barriers to sustained improvement. Participants reported positive experiences, noting increased emotional awareness and a sense of connectedness. Overall, the findings suggest that peer support interventions grounded in psychology hold promise for reducing FOMO and fostering resilience among vulnerable youth. However, continued engagement and personalised approaches are recommended to achieve greater impact in future research